External Assessment of Quality of Care in the Health Sector in Colombia - World Bank; International Finance Corporation (World Bank, Washington, DC, 2019)
This report presents findings from an assessment of quality of care in the health sector in Colombia, using a novel methodology developed by the World Bank Group to assess government oversight, promotion and stewardship of quality of care in the health sector. This assessment of quality of care in the health sector in Colombia examines how well governments strategize, plan and measure quality; set standards of care; build capacity for quality improvement in the sector; ensure adequate resources are available and well distributed to support quality results; hold organizations accountable for quality results; apply quality policies consistently; and achieve superior quality of care results. This methodology evaluates these eight domains using 49 criteria based on 171 standards. The assessment is based on quantitative analytics, key informant interviews, over 30 visits of public and private healthcare facilities, a review of key policy documents and a survey of a sample of health insurance companies. The assessment is a joint initiative from the World Bank and the International Finance Corporation (IFC) and was undertaken for the first time in Colombia. It took place from January to June 2019.